Noble lives : biographical portraits of three remarkable gay men - Glenway Wescott, Aaron Copland, and Dag Hammarskjöld - Vargo, Marc (Harrington Park, 2005)
"Noble Lives examines how sexual orientation affected the careers of two historical figures generally accepted as gay, and a third whose sexual identity was in constant question during his lifetime. This book features comprehensive biographical accounts of Jazz Age author Glenway Wescott, Academy Award-winning composer Aaron Copland, and Nobel Peace Laureate Dag Hammarskjold, addressing the relationship between their sexuality and their achievements in literature, the social sciences, musical composition, diplomacy, and global politics. Noble Lives is the first English-language text to thoroughly - and objectively - explore the troubled sexuality of Sweden's Hammarskjold, the former Secretary-General of the United States."--BOOK JACKET.